2019
DOI: 10.3390/chemosensors7020017
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization of Cotton Fabric with Fluorescent Dendrimers, Spectral Characterization, Cytotoxicity, Antimicrobial and Antitumor Activity

Abstract: Poly(propylenimine) dendrimers from first and third generations modified with 1,8-naphthalimide units and their Zn(II) complexes have been investigated by absorption and fluorescence spectroscopy. These dendrimers have been deposited on a cotton cloth by the extraction method, producing yellow-colored textile materials. They have been characterized by defining their color coordinates L*a*b*, XYZ and xy. The antimicrobial activity of dendrimers has been investigated in vitro against model gram-positive and gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…These results suggest that N-halamine modi cation do not signi cantly possess cell toxicity; the results are in agreement with other reported results for similar studies. (Demir, Cerkez et al 2015;Demir, Broughton et al 2017;Grabchev, Staneva et al 2019;Gao, Su et al 2020) However, it is also assumed that the small toxicity observed in the present experiment may due to release or dissociation of Cl + into cell medium with time from N-halamine modi ed chitosan@AgNPs-NWFC. The release can be controlled by optimizing the chlorine contents at nonwoven cotton fabric and with repeated washing with water without affecting fabricated fabric properties.…”
Section: Loaded Chlorine Content Analysismentioning
confidence: 74%
“…These results suggest that N-halamine modi cation do not signi cantly possess cell toxicity; the results are in agreement with other reported results for similar studies. (Demir, Cerkez et al 2015;Demir, Broughton et al 2017;Grabchev, Staneva et al 2019;Gao, Su et al 2020) However, it is also assumed that the small toxicity observed in the present experiment may due to release or dissociation of Cl + into cell medium with time from N-halamine modi ed chitosan@AgNPs-NWFC. The release can be controlled by optimizing the chlorine contents at nonwoven cotton fabric and with repeated washing with water without affecting fabricated fabric properties.…”
Section: Loaded Chlorine Content Analysismentioning
confidence: 74%
“…The microbiological activity of D3 is comparable with the activity against the same strains using other PAMAM and PPI dendrimers modified with 1,8-naphthalimides. [17][18][19][20][21] The antimicrobial effect of cotton fabric treated with D3 was tested against the model strains B. cereus, P. aeruginosa and C. lipolytica. We found that cotton fabric treated with D3 effectively reduced the growth of B. cereus and C. lipolytica by about 80% and 50%, respectively, and about a 20% growth reduction in P. aeruginosa was observed ( Figure 6).…”
Section: Antimicrobial Activity Of D3 and Modified Cotton Fabricmentioning
confidence: 99%
“…[12][13][14][15] Because the monomeric 1,8-naphthalimide compounds also exhibit biological activity, we have studied the antimicrobial and anticancer activity of PAMAM and PPI dendrimers and their metal complexes modified with 1,8-naphthalimides. [16][17][18][19][20][21] The deposition of such bioactive dendrimers on the surface of textile materials creates textiles with high antimicrobial activity and results in better control of biofilm formation. [22,23] Such textile materials may find application as wound dressings, hospital textiles, linen, towels, filters, and in other medical devices.…”
Section: Introductionmentioning
confidence: 99%
“…These dendrimers deposited cotton fabrics used in textile industry. (139). Sericin, a silk protein, has anticancer property.…”
Section: Textiles In Cancer Treatmentmentioning
confidence: 99%